Faktor-Faktor yang Mempengaruhi Salah Laku Pelajar-Pelajar Menengah Atas di Daerah Manjung - Mhod Shubari, L. Mat (2000)
The purpose of this study was to observe the factors which influenced the misconduct of students in the upper secondary schools in the Manjung district. This research based on Wickman model (1974) which stressed on moral misbehaviour, against the authority (teacher), the school rules, classroom rules, do not comply with the school home work, lack of cooperation and self tidyness. The misconduct factor was based on demography (sex, race, family size, family’s income and parents education status), family relationship, learning environment and school physical facilities and peer group influence. The research was conducted with 350 respondences from seven schools in Manjung Perak. From which only 295 questionaires were returned and analysed. The questionaires consist of 63 items using Likert Scale. The required data were analysed through descriptive statistic for its frequency, percent, min and standard deviation. Inferences statistic method for t-test analysis, ANOVA, Pearson corellation and regression are used to test the hypothesis. The research showed that no significant differences among the demography factor, that is sex, race, family income, family size and the education status of the mother with misconduct except factors of number of siblings and education status of the father. The results of the research also show factors of family relationship, school physical facilities, the learning environment and peer group influenced the misconduct of the students. However the learning environment factor and peer group has a little stronger relationship and significant influence toward misconduct behaviour among the upper secondary school students.